A novel clinically relevant graft‐versus‐leukemia model in humanized mice. Issue 2 (31st May 2021) - Jia, Bei; Zhao, Chenchen; Bayerl, Michael; Shike, Hiroko; Claxton, David F.; Ehmann, W Christopher; Mineishi, Shin; Schell, Todd D.; Zheng, Pan; Zhang, Yi; Shultz, Leonard D.; Prabhu, K. Sandeep; et al.
Abstract: The prognosis for acute myeloid leukemia (AML) relapse post allogeneic hematopoietic stem cell transplantation (alloSCT) is dismal. Novel effective treatment is urgently needed. Clinical benefit of alloSCT greatly relies on the graft‐versus‐leukemia (GVL) effect. The mechanisms that mediate immune escape of leukemia (thus causing GVL failure) remain poorly understood. Studies of human GVL have been hindered by the lack of optimal clinically relevant models. Here, using our large, longitudinal clinical tissue bank that include AML cells and G‐CSF mobilized donor hematopoietic stem cells (HSCs), we successfully established a novel GVL model in humanized mice. Donor HSCs were injected into immune‐deficient NOD‐Cg‐ Prkdc scid IL2rg tm1Wjl /SzJ (NSG) mice to build humanized mice. Immune reconstitution in these mice recapitulated some clinical scenario in the patient who received the corresponding HSCs. Allogeneic but HLA partially matched patient‐derived AML cells were successfully engrafted in these humanized mice. Importantly, we observed a significantly reduced (yet incomplete elimination of) leukemia growth in humanized mice compared with that in control NSG mice, demonstrating a functional (but defective) GVL effect. Thus, for the first time, we established a novel humanized mouse model that can be used for studying human GVL responses against human AML cells in vivo. This novel clinically relevant model provides a valuable platform for investigating the mechanisms of human GVL and development of effective leukemia treatments. Graphical Abstract: A novel humanized graft‐vs‐leukemia model was established by grafting human donor hematopoietic stem cells and patient‐derived acute myeloid leukemia cells into NSG mice.